PsycEXTRA Dataset 2004
DOI: 10.1037/e455162008-001
|View full text |Cite
|
Sign up to set email alerts
|

Religion in England and Wales: Findings from the 2001 Home Office Citizenship Survey: Home Office research study 274

Abstract: The Research, Development and Statistics Directorate RDS is part of the Home Office. The Home Office's purpose is to build a safe, just and tolerant society in which the rights and responsibilities of individuals, families and communities are p roperly balanced and the protection and security of the public are maintained. RDS is also part of National Statistics (NS). One of the aims of NS is to inform Parliament and the citizen about the state of the nation and provide a window on the work and perf o rm a n c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 1 publication
0
6
0
1
Order By: Relevance
“…9 In 2001, the UK Census and Home Office Citizenship Survey clearly demonstrated that it is feasible to collect valid and reliable data on ethnicity and religion, and that these data can be used for extremely important analyses. 10,11 Years on, it is time that the standard set in these national surveys is much more widely adopted within health-care services. …”
Section: Discussionmentioning
confidence: 99%
“…9 In 2001, the UK Census and Home Office Citizenship Survey clearly demonstrated that it is feasible to collect valid and reliable data on ethnicity and religion, and that these data can be used for extremely important analyses. 10,11 Years on, it is time that the standard set in these national surveys is much more widely adopted within health-care services. …”
Section: Discussionmentioning
confidence: 99%
“…The 2001 Home Office Citizenship Survey shows that while those who say they have no religion are disproportionately from the advantaged and the powerful (that is, they are more likely to be white, male and middle class) and only 17 per cent of whites say that religion is important to their self-identity, the numbers for black and South Asian respondents are 44 and 61 per cent, respectively. 12 Religion, then, is clearly an ethnic feature of Britain not just in the sense that most whites are Christians and most people of colour are not, but in terms of the personal, social and political salience and significance of religion.…”
Section: Policy Based On Religion As Identitymentioning
confidence: 99%
“…However, the expression of a religious affiliation does not connote any serious commitment to religion. An analysis of findings from the 2001 Citizenship Survey in the UK found that only 20 per cent of respondents ‘felt their religious beliefs to be an important part of their sense of self‐identity’ (O'Beirne 2004, vii). Despite this, the governments of the UK and Australia in the last decade have sought to re‐infuse religiosity into public life.…”
Section: Desecularisationmentioning
confidence: 99%